Intracranial Tuberculoma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
In a report from the Dept of Pediatrics, All India Inst of Applied Sciences, New Delhi, India, intracranial tuberculoma was found in 20 (24%) of 83 patients with partial seizures complicated by increased intracranial pressure, systemic tuberculosis or focal neurologic deficit and in 12 (22%) of 55 patients with tuberculous meningitis.